Prospective mathematic teachers’ reflective thinking in solving numeracy problems at the critical reflection stage - Reno Warni Pratiwi; Purwanto; Abd. Qohar (Jurnal Elemen, 2024)
The low numeracy skills in Indonesia are one factor affecting the quality of mathematics education, so reflective thinking is needed to improve this ability. This study aims to describe prospective mathematics teachers' reflective thinking process in solving numeracy problems at the critical reflection stage based on prior knowledge. This study used a qualitative, descriptive research methodology. The research participants were 34 prospective mathematics teachers at the State University of Malang, East Java. The instruments used are numeracy tests and interview guidelines. Data analysis includes data reduction, presentation, and conclusion drawing. The findings revealed notable differences in reflective thinking based on prior knowledge levels at the critical reflection stage. Subjects with high prior knowledge tried various solutions, were confident in their answers, and accurately drew conclusions and explained their reasons. Subjects with medium prior knowledge tried different methods but needed more confidence in their results. They could conclude but struggled to explain their reasons. Subjects with low prior knowledge used the same method, needed more confidence, and needed help explaining their reasons despite concluding. These findings imply creating a better training program for prospective mathematics teachers, emphasizing numeracy and reflective thinking growth.